Digital Transformation of Public Participation in Indonesia's Constitutional System: The Effectiveness of the Indonesian House of Representatives' Aspiration Channel as an Instrument of Participatory Democracy - Abdusyahid Naufal Fathullah; Muhamad Alief Hidayat; Andre Arya Pratama (Fakultas Hukum Universitas Lampung, 2025)
Public participation in Indonesia has increasingly shifted toward digital models following the COVID-19 pandemic, yet substantive engagement remains limited despite 221.56 million internet users and persistent urban–rural digital disparities. Using a socio-legal approach, this study examines the alignment between regulatory frameworks and digital participation practices in the Indonesian House of Representatives (DPR RI), focusing on initiatives such as DPR Now! and the Public Aspiration Agency. The findings show that participation mechanisms remain at the tokenistic consultation level on Arnstein’s Ladder, reflected in a low response rate of 3 percent, weak feedback loops, fragmented platforms, and the absence of a legal mandate to integrate public input into legislative decision-making. Comparative analysis with international models, including Decide Madrid and Taiwan, demonstrates the potential to significantly enhance participation through co-creation mechanisms supported by blockchain and AI-based sentiment analysis. Accordingly, this study proposes the establishment of Digital Deliberation Councils, regulatory harmonization, and constitutional amendments to guarantee digital participation rights, providing a foundation for a more inclusive and deliberative digital democracy in Indonesia.